Assessment of the colloidal and functional properties of soybean curd residue “okara” (Glycine max) for encapsulation - Oryan, Willaine Bless P.; Peralta, Justin Godfred B. (Quezon City University of the Philippines Diliman, 2024)
Okara is a by-product of processing soybean products, such as soymilk and soybean curd. While it is an underutilized food product that is often discarded or used as livestock feed, okara is rich in nutritional properties and shares the functional properties that soybean has. The study investigated the functional and colloidal properties of okara to utilize its potential in the food industry as a functional food ingredient, specifically as a wall material for encapsulation of bioactive compounds in food products. This was done by (1) evaluating the effects of storage temperature and pH, and (2) assessing the effects of adding sodium alginate to okara protein isolate (OPI) emulsions. OPI was extracted with a recovery of 15.20%, and it was found to have highest solubility at pH 2. OPI also had satisfactory emulsifying activity and stability indices (EAI and ESI) of 41.15 m2/g and 124.84 min, respectively. The holding capacities of OPI were lower than related studies, but these properties may be improved by optimizing processing conditions. Meanwhile, OPI also exhibited good foaming properties and bulk density. Primary emulsions were prepared by mixing OPI with medium chain triglyceride (MCT) oil. The highest EAI and ESI were obtained by emulsions at pH 8 and 6, respectively; emulsions stored at room temperature had a higher emulsifying activity, but were more stable at 4°C. All emulsions exhibited low viscosities which were significantly affected by pH and storage conditions. Those at near-neutral pH had more stability against creaming; however, both pH and storage conditions were found to have no significant effect on this property. Meanwhile, the addition of 0.02% w/v sodium alginate (SA) resulted in minimal improvements with the EAI, ESI, and colloidal properties of OPI emulsions. FTIR analysis indicated protein-polysaccharide interactions in OPI-SA emulsions which correspond with enhanced properties and stability of the emulsions.
In partial fulfillment for the Degree of Bachelor of Science in Food Technology
Thesis
Keywords: Colloids; Emulsions; Protein functionality; Encapsulation; Colloidal properties; Okara; FTIR analysis; Soybean curd residue